AN ANALYSIS ON DERIVATIONAL PROCESS OF ENGLISH NOUN IN NEWSWEEK’S ARTICLES - Misla Geubrina (BAHAS, 2018)
This research deals with the derivational process of English noun. It is one of the forming word processes. The writer focuses on derivational process of English noun which found in Newsweek’s Articles. The objectives of the study are to find out the derivational process of English noun included in Newsweek’s Articles, to show the derivational process of English noun contained in Newsweek’s Articles and to show the dominant of derivational process of English noun in Newsweek’s Articles. Specifically, this research tries to analyze derivational process of English noun which attach to the word that exist in Newsweek’s Articles. The derivational process of English noun can be attaches to the verb, adjective and noun. From the analysis, it is found that 69 derivational suffixes of English noun, and the dominant derivational process of English noun found in Newsweek’s Articles is suffix –tion with the percentage 17,39 % of all derivational process of English noun which had been found in Newsweek’s Articles. And followed by suffix –er or –or with 14,49 % and suffix –ity with 13,04 %.  This research made based on the library and other sources, as there are many available sources is collected to support this research.